Effects of Nandrolone Decanoate on Skeletal Muscle and Neuromuscular Junction of Sedentary and Exercised Rats - Tibúrcio, Felipe Cantore [UNESP] (2023)
Background and Objectives: Nandrolone decanoate (ND) is the most widely used among the anabolic androgenic steroids (AAS), synthetic substances derived from testosterone, to improve muscular and health gains associated with exercises. The AAS leads to physical performance enhancement and presents anti-aging properties, but its abuse is associated with several adverse effects. Supraphysiological doses of AAS with or without physical exercise can cause morphological and functional alterations in neuromuscular interactions. This study aims to investigate the effects of ND supraphysiological doses in neuromuscular interactions, focusing on the soleus muscle and its neuromuscular junctions (NMJs) in rats, associated or not with physical exercise. Materials and Methods: Forty male Sprague Dawley rats were divided into four groups: sedentary and exercised groups, with or without ND at the dose of 10 mg/kg/week. The animals were treated for eight weeks, with intramuscular injections, and the soleus muscle was collected for morphological analyses. Results: The supraphysiological doses of ND in the sedentary group caused muscle degeneration, evidenced by splitting fibers, clusters of small fibers, irregular myofibrils, altered sarcomeres, an increase in collagen deposition and in the number of type I muscle fibers (slow-twitch) and central nuclei, as well as a decrease in fibers with peripheral nuclei. On the other hand, in the ND exercise group, there was an increase in the NMJs diameter with scattering of its acetylcholine receptors, although no major morphological changes were found in the skeletal muscle. Thus, the alterations caused by ND in sedentary rats were partially reversed by physical exercise. Conclusions: The supraphysiological ND exposure in the sedentary rats promoted an increase in muscle oxidative pattern and adverse morphological alterations in skeletal muscle, resulting from damage or post-injury regeneration. In the ND-exercised rats, no major morphological changes were found. Thus, the physical exercise partially reversed the alterations caused by ND in sedentary rats.